Needs Analysis of English For Specific Purposes (ESP) for the Students of Business and Economics Faculty (FEB) UNISBANK Semarang - Sugeng Purwanto (Universitas Stikubank (UNISBANK) Semarang, 2014)
The Study aims at investigating a possible reconstruction of ESP for the students of FEB Unisbank Semarang in anticipation of the needs for English in Asean Economic Community (AEC) Era 2015. Respondents were the faculty officers and ex-officer, ESP lecturers and randomly selected students to justify the proposed ESP under Cambridge Proficiency Level B2. The findings indicate that the majority of respondents expressed positive responses on which to formulate the Competency Standards required of the students in order to professionally survive in the AEC Era. Recommended in the study is to reconstruct the ESP Syllabus and teaching materials. Key Words: ESP, standard competency, syllabus